Behavioral and neurochemical evaluation of ethanol on olanzapine treated methylphenidate induced manic like behaviors in swiss albino mice - Thangavel Tamilselvan; Saiful Alom Siddique; Manikannan Vishnupriya; Ganapathy Sindhu; Elumalai Balamurugan (Beni-Suef University Journal of Basic and Applied Sciences, 2017)
The present study was aimed to evaluate the effect of olanzapine (OLZ) with ethanol (EtOH) on methylphenidate (MPD) induced mania in Swiss albino mice. The effect of EtOH on OLZ treated MPD induced mice by analysing the behavioral activities in open field test (OFT), forced swimming test (FST) and the neurotransmitter levels for Dopamine (DA), Norepinephrine (NE), serotonin (5-HT) and γ-Aminobutyric acid (GABA). We assayed by considerably found that repeated administration of MPD (2 mg/kg b.w) produced hyperactivity. MPD induced manic like behavioral was manifested by the increased locomotor activities in open field test (central, peripheral and rearing in 5 min). In forced swim test (FST) increased swimming and decreased immobility time (5 min) in MPD treated mice. In fluorimetric micromethod, MPD administrated mice increased DA, NE, 5-HT levels and decreased the GABA levels in the PFC on 21 days. The results of the present study reported that the OLZ treated mice controlled the mania like behavioral activities and neurotransmitter levels in MPD subjected mice. EtOH enhanced the locomotor activities, immobility time, DA, NE and GABA levels. In addition, EtOH reduced swimming and 5-HT level of the brain. From this result EtOH impairs the OLZ treatment and enhanced the locomotor activity and did not prevent neurotransmitter levels in brain tissue. Further studies will be needed to discover the mechanisms responsible for these findings.